Divergent drivers of the microbial methane sink in temperate forest and grassland soils. (22nd November 2020) - Täumer, Jana; Kolb, Steffen; Boeddinghaus, Runa S.; Wang, Haitao; Schöning, Ingo; Schrumpf, Marion; Urich, Tim; Marhan, Sven
Abstract: Aerated topsoils are important sinks for atmospheric methane (CH4 ) via oxidation by CH4 ‐oxidizing bacteria (MOB). However, intensified management of grasslands and forests may reduce the CH4 sink capacity of soils. We investigated the influence of grassland land‐use intensity (150 sites) and forest management type (149 sites) on potential atmospheric CH4 oxidation rates (PMORs) and the abundance and diversity of MOB (with qPCR) in topsoils of three temperate regions in Germany. PMORs measurements in microcosms under defined conditions yielded approximately twice as much CH4 oxidation in forest than in grassland soils. High land‐use intensity of grasslands had a negative effect on PMORs (−40%) in almost all regions and fertilization was the predominant factor of grassland land‐use intensity leading to PMOR reduction by 20%. In contrast, forest management did not affect PMORs in forest soils. Upland soil cluster (USC)‐α was the dominant group of MOBs in the forests. In contrast, USC‐γ was absent in more than half of the forest soils but present in almost all grassland soils. USC‐α abundance had a direct positive effect on PMOR in forest, while in grasslands USC‐α and USC‐γ abundance affected PMOR positively with a more pronounced contribution of USC‐γ than USC‐α. Soil bulk density negatively influenced PMOR in both forests and grasslands. We further found that the response of the PMORs to pH, soil texture, soil water holding capacity and organic carbon and nitrogen content differ between temperate forest and grassland soils. pH had no direct effects on PMOR, but indirect ones via the MOB abundances, showing a negative effect on USC‐α, and a positive on USC‐γ abundance. We conclude that reduction in grassland land‐use intensity and afforestation has the potential to increase the CH4 sink function of soils and that different parameters determine the microbial methane sink in forest and grassland soils. Abstract : We measured potential atmospheric methane oxidation rates in 299 forest and grassland soils and found that different parameters determine the microbial methane sink in forests and grasslands. Methane oxidation rates were two times higher in forest than in grassland soils and the methanotrophic community differed, with Upland soil cluster (USC)‐α being more prevalent in forests and USC‐γ in grassland soils. High land use intensity had a negative effect on potential atmospheric methane oxidation rates (−40%) in grassland soils. We conclude that reduction in grassland land‐use intensity and afforestation has the potential to increase the methane sink function of soils.